Increasing sustainability within theracking system industry: An exploration in how to achieve an environmental and business sustainable solution at Modul-System - Bales, Glen; Fiedler, Bernard (My University, 2020)
This project has had as a purpose to develop a new service concept for racking systems, used in light commercial vehicles, that meets the future needs for electrical vehicles (EVs) and results in a more sustainable service. It has been conducted by two students performing their master thesis at Chalmers University product development masters programme, in collaboration with the company Modul-System. Included in the report is a pre-study, exploring the literature around environmental sustainability, electric vehicles and outsourcing. The market, its trends and actors are analysed. An iterative concept generation phase is also conducted. The main focus has been in exploring and evaluating a broad spectrum of different business models, resulting in two concepts, Re-use and Optimise use, being produced and further detailed. Re-Use is a business oriented concept, which through circular economy, aims to increase the racking systems’ life span. It achieves this in two ways. Firstly, through re-use of racking systems for the first hand customer, moving the racking systems from a vehicle, that is going to be retired, to a new one. Secondly, through refurbishment and sales of used racking systems to a second hand customer, targeting the low price segment of the market. Emphasis on how to realise the refurbishment of the racking systems is included in the later stages of concept development. Optimise use focuses on integrating hardware and software solutions, to increase the effective range of electric vans with racking systems installed. It also aims to increase resource utilisation efficiency. The main features are (1) a material management system, (2) a fleet management system adapted for EVs and (3) removable/mobile racking systems. The material management system aims to minimise the material that the customer brings to the work sites by integrating both physical and software solutions. The fleet management system includes new functions adapted for EV use that facilitates work optimisation from a fleet perspective and monitoring of individual vehicles/drivers. The removable racking systems will facilitate material exchange and allow the customers to charge their vehicles while they perform their work tasks. It is also concluded that that the purpose of the project is fulfilled, but further analysis and development is necessary to fully implement the two concepts. A conclusive recommendation for how to proceed with the development of both concepts is thus lastly presented, including a pilot program for the Re-use concept and recommendations for future master thesis projects.
Keywords: Circular economy, Sustainability, Servitisation, Electric vehicles; Racking systems, Fleet management